EMPLOYEE PERFORMANCE ANALYSIS IN THE DISTRICT OF TULUNG KLATEN - Purwanti, Dyah Arsih; Mursito, Bambang; Sudarwati, Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The research that has been done has the aim of knowing the influence of motivation, discipline, work environment and employee ability on a variable called employee performance in Tulung District, Klaten Regency. This research that has been done uses an approach called quantitative. The population in this study consisted of all employees in Tulung District, Klaten Regency, all of whom were 52 people. The sampling technique uses saturated samples. The technique for data analysis in this research that has used an analysis called multiple linear regression. The results of a study that has been conducted show that motivation, discipline, work environment and employee abilities have a positive and significant impact on the variable called employee performance in Tulung District, Klaten Regency. It is hoped that in the future, Tulung District, Klaten Regency, will continue to maintain and improve the quality of motivation, discipline, work environment and existing employee abilities, so that employee performance will also continue to increase and of course be better than before. Keywords: Employee Performance, Motivation, Discipline, Work Environment, Employee Ability